Bunt i nostalgia. Filmy dokumentalne o festiwalu w Jarocinie - Bitka, Stanisław (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
The aim of the article is to present and attempt to classify documentary films about the Jarocin music festival. The films are conventionally divided into those shot during the 1980s editions and those created in our century, which describe them festival in retrospect. By analyzing selected works, the author draws attention to whether and how the approach to the subject and the form of the film change over the years.